Loose architectural fragments on Harsha Hill - Temples of India Project Team (Jio Institute, 2024)
It seems that the beam, richly carved with human figures, was likely placed on the varandika of the temple, the adjoining portions between the temple walls and the spire. The protruding offsets typically feature mithuna figures inside the niches, while the recess between the two offsets is beautifully carved with images of apsaras or women engaged in different actions such as carrying children, weapons, etc. The male figures are often portrayed with weapons and accompanied by female companions. This fragment is one of the loose architectural fragments on Harsha Hill.